Epidemiology of acute otitis in pediatric patients - Maddalena Perotti (Microbiologia Medica, 2011)
Introduction. Acute otitis is one of the most common pediatric infectious diseases that requires an accurate diagnosis in order to direct appropriate therapy to reduce the risk of complications. In this study pathogens collected from pediatric patients and their antibiotic susceptibility patterns were evaluated. Methods. Between May 2009 and May 2010, 739 samples (swabs taken from nasopharynx in case of acute otitis media and/or from ears in case of acute external otitis, collected from 680 patients, suffering of otalgia, admitted to the emergency department of our Hospital were studied.The specimens were submitted for routine bacterial cultures and the susceptibility tests were performed according to Clinical Laboratory Standards. Nitrocefin was used to detect ß-lactamase activity. Results. 316 samples (42.8%) of 739 were negative, 102 (13.8%) were positive for Streptococcus pneumoniae, 97 (13.1%) for Moraxella catarrhalis, 68 (9.2%) for Haemophilus influenzae, 62 (8.4%) for Pseudomonas aeruginosa, 49 (6.6%) for Staphylococcus aureus, 36 (4.9%) for Streptococcus pyogenes, 5 (0.7%) for Gram negative and 4 (0.5%) for Candida spp. Antibiotic susceptibility tests showed that amikacin, ceftazidime, ciprofloxacin, imipenem, meropenem and piperacillin/tazobactam were active against all Gram negative strains isolated.We found one strain of MRSA. Of 102 Streptococcus pneumoniae, 5 (4.9%) were penicillin resistant and 25 (24.5%) were erythromycin resistant, showing the prevalence of constitutive phenotype (80%). All M. catarrhalis strains were ß-lactamase producers while all H. influenzae were ß-lactamase negatives. Conclusions. The prevalent etiological agents in pediatric acute otitis are S. pneumoniae, M. catharralis, and H. influenzae, as reported in literature. In external acute otitis P. aeruginosa prevails in particular in summer.